Peran E-commerce dalam menggerakkan UMKM di Indonesia - SAMSUDIN, MOCH NADZARUDIN (Maliki Interdisciplinary Journal, 2026)
The rapid advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt by integrating e-commerce as a fundamental strategy to strengthen their competitiveness. This study examines how digitalization and the adoption of e-commerce influence economic growth and drive business transformation within Indonesian MSMEs. Using a literature review approach, the research analyzes scholarly articles that discuss MSME development in the digital era. The results indicate that digitalization plays a crucial role in enhancing operational efficiency, widening market access, and accelerating revenue growth. Additionally, the adoption of e-commerce reshapes business practices, particularly in marketing strategies, supply chain management, and customer service models. Despite these advantages, MSMEs continue to face obstacles such as limited digital literacy and uneven technological access. Overall, the study emphasizes that digitalization is a key driver in strengthening MSMEs and supporting broader national economic growth.